2021
DOI: 10.3389/fnagi.2021.727590
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Alterations in Vascular Dementia: Emphasis on Risk Factors

Abstract: Vascular dementia (VaD) constitutes the second most prevalent cause of dementia in the world after Alzheimer’s disease (AD). VaD regroups heterogeneous neurological conditions in which the decline of cognitive functions, including executive functions, is associated with structural and functional alterations in the cerebral vasculature. Among these cerebrovascular disorders, major stroke, and cerebral small vessel disease (cSVD) constitute the major risk factors for VaD. These conditions alter neurovascular fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 414 publications
(581 reference statements)
0
28
0
4
Order By: Relevance
“…Major efforts have been invested in the past decade to understand the role of vascular risk factors in AD etiology, pathogenesis and progression (9)(10)(11). The overwhelming observations clearly outlined an increased risk of cerebral microinfarct incidence associated with vascular pathologies in AD patients (26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major efforts have been invested in the past decade to understand the role of vascular risk factors in AD etiology, pathogenesis and progression (9)(10)(11). The overwhelming observations clearly outlined an increased risk of cerebral microinfarct incidence associated with vascular pathologies in AD patients (26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…The neuropathology of AD is characterized by the deposition of amyloid-b (Ab) plaques associated to Ab accumulation, and the formation of neurofibrillary tangles (NFTs) associated to tau hyperphosphorylation, leading to brain atrophy caused by the loss of neurons and synapses (5)(6)(7)(8). Deregulation of the innate immune response as well as the cerebrovascular functions are now well recognized as main components of AD etiology, pathogenesis and progression (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, neuronal damage will further activate microglia and induce pro-inflammatory cytokine release, exacerbating neuronal inflammation and reducing neuronal survival ( Qu et al, 2021 ). Meanwhile, the breakdown of blood–brain barrier leads to the penetration of plasma proteins, neurotoxic compounds, and peripheral immune cells into the brain, which aggravates the damage and eventually causes neurological defects ( Lecordier et al, 2021 ). The GSK3β/β-catenin signaling pathway plays an important role in numerous biological processes including neuronal cell growth and proliferation and is also regarded as an important signaling pathway in the pathological mechanism of VD ( Foulquier et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following many previous syntheses on the topic, the most recent [51] continues to demonstrate an increased risk of cognitive decline particularly from increasing PM2.5, whereas the associations with dementia, and from other pollutants are less consistent. Specific patterns of cognitive profiles associated with the highest exposure to multiple air pollutants, and neuroimaging studies, have shown incongruenties [52 ▪ ,53–55].…”
Section: Epidemiological Associations Between Air Pollutants and Ment...mentioning
confidence: 99%